2010
DOI: 10.1111/j.1540-8159.2009.02566.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Appropriate Implantable Cardioverter Defibrillator (ICD) Therapy in Primary Prevention Patients with Ischemic and Nonischemic Cardiomyopathy

Abstract: ICD-delivered therapy occurred in 19% of primary prevention patients with both ischemic and dilated cardiomyopathy and was predicted by NSVT and a lack of beta-blocker use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 38 publications
3
35
1
Order By: Relevance
“…Ninety-four episodes of VF were observed in four Chagas and 7 episodes of VF in two non-Chagas cardiomyopathy patients (p = 0.03). Median time to first event was 78 The frequency of shock occurrence observed in our Chagas cardiomyopathy cohort in this study was similar to that reported in patients with non-Chagas cardiomyopathy [3]. The lower mortality rate observed in our study in comparison to studies of secondary prevention of SCD [4] in Chagas disease patients may partially be explained by the lower frequency of shock occurrence.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Ninety-four episodes of VF were observed in four Chagas and 7 episodes of VF in two non-Chagas cardiomyopathy patients (p = 0.03). Median time to first event was 78 The frequency of shock occurrence observed in our Chagas cardiomyopathy cohort in this study was similar to that reported in patients with non-Chagas cardiomyopathy [3]. The lower mortality rate observed in our study in comparison to studies of secondary prevention of SCD [4] in Chagas disease patients may partially be explained by the lower frequency of shock occurrence.…”
supporting
confidence: 88%
“…Median of episodes per patient was 6.5 (3,38). Ninety-four episodes of VF were observed in four Chagas and 7 episodes of VF in two non-Chagas cardiomyopathy patients (p = 0.03).…”
mentioning
confidence: 99%
“…Our finding that diabetes mellitus is associated with an increased risk of appropriate therapy supports 2 previous studies, 7,11 but compared with the predictors of appropriate therapy previously found in the larger trials such as Multicenter Automatic Defibrillator Implantation Trial II (MADIT-II), Multicenter Automatic Defibrillator Implantation Trial With Cardiac Resynchronization Therapy (MADIT-CRT), Comparison of Medical Therapy, Pacing, and Defibrillation in Heart Failure (COMPANION), Resynchronization Reverses Remodeling in Systolic Left Ventricular Dysfunction (REVERSE), Cardiac Resynchronization-Heart Failure (CARE-HF), and others, this is a novel finding. [12][13][14][15][16][17][18][19][20][21] Our explanation for the risk association of diabetes mellitus with appropriate ICD therapy includes a vulnerable myocardium resulting from fibrosis, ischemia, and scar tissue; reduced autonomic function; and reduced coronary circulation in diabetics, [22][23][24][25] rendering the myocardium more prone to produce ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of appropriate therapy in their study was about 19%. 15 The frequency of NSVAs in the present study was about 54.8% which may to some degree justify the relatively high incidence of SVAs.…”
mentioning
confidence: 72%